Getting the phenotypes right: an essential ingredient for understanding aetiological mechanisms underlying persistent violence and developing effective treatments - Hodgins, Sheilagh; De Brito, Stephane A.; Simonoff, Emily; Vloet, Timo; Viding, Essi (Frontiers in Behavioral Neuroscience, 2009)
In order to reduce societal levels of violence, it is essential to advance understanding of the neurobiological mechanisms involved in initiating and maintaining individual patterns of physical aggression. New technologies such as Magnetic Resonance Imagining and analyses of DNA provide tools for identifying these mechanisms. The reliability and validity of the results of studies using these tools depend not only on aspects of the technology, but also on the methodological rigour with which the studies are conducted, particularly with respect to characterizing the phenotype. The present article discusses five challenges confronting scientists who aim to advance understanding of the neurobiological mechanisms associated with persistent violence. These challenges are: (1) to develop evidence-based hypotheses and to design studies that test alternate hypotheses; (2) to recruit samples that are homogeneous with respect to variables that may be linked to neurobiological mechanisms underpinning violent behaviour; (3) to use reliable and valid measures in order to fully characterize participants so that the external validity of the results is evident; (4) to restrict the range of age of participants so as not to confuse developmental change with group differences; and (5) to take account of sex. Our goal is to contribute to elevating methodological standards in this new field of research and to thereby improve the validity of results and move closer to finding effective ways to reduce violence